Laurent, Muriel. Contrabando, poder y color en los albores de la República. Nueva Granada, 1822-1824. Bogotá: Ediciones Uniandes, 2014. 440 pp. - Díaz, Carlos A.; Universidad Nacional de Colombia (2016)
null